(untitled) (LIS TODAY, 2026)
This paper is an analysis of the journal Library Herald’s contribution to library science from 2015 to 2024. A total of 338 articles were included in this study. The research will focus on drawing out the trends, major areas of research, and the influence of the journal on the development of research in the library science field. Using specific terms and methods, we assessed the number of publications, authorship, authorship partnerships, article publication by year, and paper classification by professional category, which are covered by this study. The analysis demonstrates that the journal is gaining more and more recognition and is one of those participating in the spread of research findings of critical value. This review identifies the journal Library Herald as one of the most important channels in enhancing the quality and standards of teaching and research, and it provides an understanding of its contribution and the future formulation of research in this rapidly developing field. This abstract provides a brief background of the study, its methodology, major findings, and how the journal Library Herald is relevant to research productivity.